Management : - Rue, Leslie W. (McGraw-Hill Irwin, 2009)
This introductory management text covers foundations and contemporary issues, planning, and organizing, directing, and controlling skills, and features color photos, chapter previews, corporate examples, margin glossaries, case studies, and questions and exercises.